The foundation and principles of critical thinking - Ali, Muhammad Mumtaz (International Institute of Islamic Thought, 2016)
This article explains the currently dominant paradigm of critical thinking, which is considered universally applicable, in terms of applying various skills, techniques, standards, and procedures. However, it also contends that emphasizing the technical aspects does not make it critical thinking, for that depends mainly upon its own metaphysical premise is more important than the skills and techniques, as it is intimately related to the technical dimensions of critical thinking. I argue that without a true and realistic metaphysical foundation, critical thinking cannot produce good results.